2020
DOI: 10.3390/jcs4040174
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine-Coated Paraffin Microcapsules as a Multifunctional Filler Enhancing Thermal and Mechanical Performance of a Flexible Epoxy Resin

Abstract: This work focuses on flexible epoxy (EP) composites containing various amounts of neat and polydopamine (PDA)-coated paraffin microcapsules as a phase change material (PCM), which have potential applications as adhesives or flexible interfaces with thermal management capability for electronics or other high-value-added fields. After PDA modification, the surface of PDA-coated capsules (MC-PDA) becomes rough with a globular appearance, and the PDA layer enhances the adhesion with the surrounding epoxy matrix, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…In fact, the melting signal is observable in both UV-crosslinked samples as a step in and and, for PEO-XL-C, also as a small peak in This signal is evident between 75 °C and 80 °C for PEO-XL-E and at a slightly higher temperature (between 80 °C and 85 °C) for PEO-XL-C. Interestingly, DMTA allowed monitoring the behavior of the PCM across the phase transition and investigating the impact of this transition on the viscoelastic parameters, which is an uncommon application for DMTA. Similar results have already been observed in previous works of our group [ 49 , 50 , 51 , 52 , 53 ] dealing with polymer-matrix composites containing an organic solid-liquid PCM. The present work demonstrated that this technique can be applied also to a shape-stabilized PCM by itself, which, to the best of the authors’ knowledge, has never been reported before in the open scientific literature.…”
Section: Resultssupporting
confidence: 91%
“…In fact, the melting signal is observable in both UV-crosslinked samples as a step in and and, for PEO-XL-C, also as a small peak in This signal is evident between 75 °C and 80 °C for PEO-XL-E and at a slightly higher temperature (between 80 °C and 85 °C) for PEO-XL-C. Interestingly, DMTA allowed monitoring the behavior of the PCM across the phase transition and investigating the impact of this transition on the viscoelastic parameters, which is an uncommon application for DMTA. Similar results have already been observed in previous works of our group [ 49 , 50 , 51 , 52 , 53 ] dealing with polymer-matrix composites containing an organic solid-liquid PCM. The present work demonstrated that this technique can be applied also to a shape-stabilized PCM by itself, which, to the best of the authors’ knowledge, has never been reported before in the open scientific literature.…”
Section: Resultssupporting
confidence: 91%
“…The adhesion between the outer PCM shell and the epoxy matrix is not optimal and this is better observed on higher-magnification micrographs (not reported for brevity). However, the fact that most PCM microcapsules are broken suggests that the fracture propagates across the microcapsules and not at the interface with the epoxy matrix [ 45 , 46 ]. In any case, the low interfacial adhesion could represent a drawback of the proposed system and will be addressed in future research.…”
Section: Resultsmentioning
confidence: 99%
“…Thermal energy storage (TES) systems have received much attention in recent years, due to the increasingly serious energy crisis and environmental problems [ 1 , 2 ]. It is reported that, on a global scale, total primary energy supply was 573 EJ and final consumption was 394 EJ per year, with around 31% energy was lost [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most attractive term for the working media of latent heat storage systems is phase-change materials (PCMs), because they do not require external energy input, are low cost, and can meet the heat storage requirements over a wide temperature range [ 6 ]. Even with these advantages, leakage and erosion issues seriously restrict the direct application of bulk PCMs unless they are enclosed or encapsulated upon melting or evaporation [ 2 , 7 ].…”
Section: Introductionmentioning
confidence: 99%